Brucellosis : Clinical and hematological study at a general hospital - Loayza, Nancy (1996)
Study of 58 patients with brucellosis hospitalized at «Dos de Mayo» Hospital from June 1994 through June 1996. Forty patients were men (69%) and eighteen women (31 %). Median age was 33,2 years (range 14-81 years) and 41 patients were less than 40 years old (70.7%). Most frequent symptoms were fever ¡n 56 patients (96,6%), articular involvement in 35 (60,3%), splenomegaly ¡n 32 (55,2%), lymphadenopathy ¡n 30 (51,7%), hepatomegaly in 28 (48,3%), headache in 24 (41,4%), pallor ¡n 20 patients (34,5%) and bleeding complications in 11 (19%). Liver was involved ¡n 5 patients. Hematologic changes were anemia in 43 patients (74,1%), lymphopenia ¡mi 13 (22,4%), thrombocytopenia ¡n 9 (15,5%), leukopenia ¡n 6 (10,3%) and pancytopenia ¡n 2 patients (3,5%). Study of bone marrow ¡n 36 patients showed normocellular or hiperplasic findings with increase of histiocytes and slight to moderate cellular phagocytosis.